2022
DOI: 10.1037/dhe0000319
|View full text |Cite
|
Sign up to set email alerts
|

Tracing roots of attitudes toward race and affirmative action among immigrant Chinese Americans: Learning from undergraduate international students.

Abstract: Immigrant Chinese Americans made the recent polling news by being the least racially tolerant in comparison to other Asian American groups over redistributive issues such as college admissions. Rather than treating Chinese immigrants as of monolithic interests and ultimately unassimilable, this study seeks to provide a more nuanced understanding of the contours and sources of their racial attitudes and beliefs. How do new immigrants from China think of issues of race, race relations, and notions of racial equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…At the same time, international students are not empty vessels when it comes to issues of race and racism—they bring racial beliefs, attitudes, and stereotypes that were formed both before and upon their arrival in the United States. Furthermore, contrary to the common perception that views international students as temporary sojourners, many international students are prospective U.S. immigrants and citizens whose racial ideologies and beliefs contribute to shaping the racial climate and public opinions on U.S. college campus and in society at large (Lien, 2021). For example, in a study conducted with 47 Asian international students primarily from East Asian countries at the University of California, Los Angeles (UCLA), Zachary Ritter (2015, 2016) found that students bring with them racial stereotypes and prejudices to U.S. college campuses that were shaped by global white supremacy and a U.S. racial hierarchical script due to exposure to media as well as transnational communication with families and friends in the United States.…”
Section: Active Contributors To Racial Dynamics and Climates On Us Co...mentioning
confidence: 97%
“…At the same time, international students are not empty vessels when it comes to issues of race and racism—they bring racial beliefs, attitudes, and stereotypes that were formed both before and upon their arrival in the United States. Furthermore, contrary to the common perception that views international students as temporary sojourners, many international students are prospective U.S. immigrants and citizens whose racial ideologies and beliefs contribute to shaping the racial climate and public opinions on U.S. college campus and in society at large (Lien, 2021). For example, in a study conducted with 47 Asian international students primarily from East Asian countries at the University of California, Los Angeles (UCLA), Zachary Ritter (2015, 2016) found that students bring with them racial stereotypes and prejudices to U.S. college campuses that were shaped by global white supremacy and a U.S. racial hierarchical script due to exposure to media as well as transnational communication with families and friends in the United States.…”
Section: Active Contributors To Racial Dynamics and Climates On Us Co...mentioning
confidence: 97%
“…Especially during the COVID-19 pandemic, they are simultaneously positioned as scapegoats, bearers of disease, cash cows, and political pawns (Yao & George Mwangi, 2022). In addition, Chinese students are considered outsiders in U.S. domestic issues, such as the Black Lives Matter movement and affirmative action campaigns (Lien, 2021), so their misunderstanding and stereotypes about U.S. racial minorities do not reduce but probably deepen due to the lack of cross-racial interactions and almost the absence of antiracist education. In short, Chinese international students' knowledge of race and class is jointly shaped by their socialization in mainland China and by their lived experiences in the United States.…”
Section: Chinese International Students' Knowledge Of Race and Classmentioning
confidence: 99%
“…Educational scholars interested in the political beliefs of international students in the United States have focused almost exclusively on the host society (e.g., Lien, 2021; Mitchell et al, 2017; Ritter, 2016), overlooking the ways in which these students’ political understanding and ideological stances were internalized through their political socialization before their cross-border mobility. In bridging the local with the global, I draw on transnationalism theory in anthropology (Ong, 1999) to systematically examine how a wealthy and privileged group of Chinese migrants engage in “flexible citizenship” (p. 1) to develop a sense of their aspirations and negotiate their lived experiences abroad in a range of diverse and complicated ways.…”
Section: Theoretical Frameworkmentioning
confidence: 99%